Glycated Hemoglobin Level and Mortality in a Nondiabetic Population with CKD - Trivin, Claire (Clin J Am Soc Nephrol, 2015)
BACKGROUND AND OBJECTIVES: Glycated hemoglobin (HbA(1c)) is used to diagnose diabetes mellitus (DM) and guide its management. The association between higher HbA(1c) and progression to ESRD and mortality has been demonstrated in populations with DM. This study examined the association between HbA(1c) and these end points in a population with CKD and without DM. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: In the hospital-based NephroTest cohort study, measured GFR (mGFR) was taken by (51)Cr-EDTA renal clearance and HbA(1c) in 1165 adults with nondialysis CKD stages 1–5 and without DM between January 2000 and December 2010. The median follow-up was 3.48 years (interquartile range, 1.94–5.82) for the competing events of ESRD and pre-ESRD mortality. Time-fixed and time-dependent Cox models were used to estimate hazard ratios (HRs) for ESRD and mortality according to HbA(1c), treated continuously or in tertiles. RESULTS: At inclusion, the mean mGFR was 42.2±19.9 ml/min per 1.73 m(2), and the mean HbA(1c) value was 5.5%±0.5%. During follow-up, 109 patients died, and 162 patients reached ESRD. Pre-ESRD mortality was significantly associated with HbA(1c) treated continuously: for every 1% higher HbA(1c), the crude HR was 2.16 (95% confidence interval [95% CI], 1.27 to 3.68), and it was 1.85 (95% CI, 1.05 to 3.24) after adjustment for mGFR and other risk factors of death. After excluding incident diabetes over time, the updated mean of HbA(1c) remained significantly associated with higher mortality risk: adjusted HR for the highest (5.7%–6.4%) versus the lowest tertile (<5.3%) was 2.62 (95% CI, 1.16 to 5.91). There was no association with ESRD risk after adjustment for risk factors of CKD progression. CONCLUSIONS: In a CKD cohort, HbA(1c) values in the prediabetes range are associated with mortality. Such values should be therefore included among the risk factors for negative outcomes in CKD populations.